Real-world effectiveness and safety of sodium-glucose co-transporter 2 inhibitors in chronic kidney disease - Supattra Hunsuwan; Sarinya Boongird; Atiporn Ingsathit; Wanchana Ponthongmak; Nattawut Unwanatham; Gareth J McKay; John Attia; Ammarin Thakkinstian (Scientific Reports)
Abstract Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have shown efficacy in clinical trials for slowing chronic kidney disease (CKD) progression, but real-world data in diverse populations are limited. This retrospective study evaluated the effectiveness and safety of SGLT2i versus renin-angiotensin-aldosterone system (RAAS) blockade in CKD patients. Data from Ramathibodi Hospital (2010–2022) were analyzed, including 6,946 adults with CKD stages 2–4, with and without diabetes, who received SGLT2i (n = 1,405) or RAAS blockade (n = 5,541) for at least three months. Patients were matched 1:4 by CKD stage and treatment initiation date. A weighted Cox proportional hazards model with inverse probability weighting assessed the effect on composite major adverse kidney events (MAKEs), including eGFR decline ≥ 40%, progression to CKD stage 5, dialysis initiation, and cardiovascular or kidney death. SGLT2i therapy was associated with a lower risk of composite MAKEs (HR: 0.59; 95% CI: 0.36–0.98; P = 0.041) and less frequent progression to CKD stage 5 (HR: 0.52; 95% CI: 0.34–0.80; P < 0.003). Adverse event rates were similar between groups, with lower urinary tract infection incidence in the SGLT2i group. These findings suggest SGLT2i therapy might reduce adverse kidney outcomes in CKD patients, regardless of diabetic status, with a favorable safety profile.